Pengaruh pemberian beberapa jenis pupuk kandang terhadap tinggi tanaman, panjang daun dan lebar daun rumput gajah (pennisetum purpureum) cv. Taiwan - Fitri, Yulita; Mega Sari, Rica; Akbar, Syahro Ali (Program Studi peternakan, 2023)
The aim was to determine the effect of applying several types of manure on plant height, leaf length and leaf width of elephant grass (Pennisetum purpureum) cv.Taiwan. This study used a completely randomized design with 4 treatments and 6 replications. This study used 24 strokes of CV Taiwan elephant grass, 24 polybags, acid soil, cow, chicken and goat manure. If the F calculated for the treatment is greater than the F table then a further DNMRT test is carried out. This research was conducted in a green house located in Koto Baru, Kubung District, Solok Regency. From the research results it was found that the application of several types of manure had a very significant effect (P<0.01) on plant height, leaf length and leaf width of elephant grass (Pennisetum purpureum) cv.Taiwan. However, there was no significant effect (P>0.05) on different types of manure (cow, goat and chicken manure). But judging from the numbers, manure that comes from goats provides higher yields.